Antibiotic utilization in open fractures - Yousif Atwan, MD; Theodore Miclau, MD; Emil H. Schemitsch, MD, FRCSC; David Teague, MD (OTA International, 2020)
Abstract. Open fractures are complex presentations with elevated risks of infection and nonunion due to a multitude of factors. Along with early surgical debridement, antibiotics have been heavily utilized and have become part of standard of care to reduce the risks of fracture-related infections. Many aspects of their use have been studied and debated. The early administration of intravenous antibiotics has been shown to significantly reduce the incidence of infection. Furthermore, current standards do not recommend prolonged antibiotic administration post wound closure. Recently, an increasing number of studies have assessed the utility of locally administered antibiotics. Clinical and basic science studies have been relatively supportive of their usage, but further studies are still warranted to further delineate their effects.